2023
DOI: 10.1186/s12889-023-15140-w
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multiple regression investigating factors associated with depressive symptoms in the middle-aged and elderly undergoing haemodialysis

Abstract: Background Depressive moods are commonly seen in patients who receive haemodialysis. This can cause a lack of compliance in their treatment procedures and increase the rate of hospitalization. This study aimed to investigate the relationship between social support and degree of depression in middle-aged and elderly patients undergoing haemodialysis and the predictors of depressive symptoms. Methods A cross-sectional correlational study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(55 reference statements)
2
0
0
Order By: Relevance
“…The study's hierarchical regression analysis demonstrates that the inclusion of each block of variables significantly raises R 2 thus emphasizing the multifactorial nature of quality of life in relation to pressure ulcers. This observation is consistent with the comprehensive model of care 34 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study's hierarchical regression analysis demonstrates that the inclusion of each block of variables significantly raises R 2 thus emphasizing the multifactorial nature of quality of life in relation to pressure ulcers. This observation is consistent with the comprehensive model of care 34 …”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with the comprehensive model of care. 34 Our logistic regression analysis corroborated the results obtained by Vecin (2022), placing emphasis on the importance of targeted interventions and highlighting age, mobility level and comorbidity count as significant predictors of pressure ulcer recurrence. 35 Our research provides significant contributions regarding the psychological ramifications of pressure ulcers for both patients and their caregivers.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the mean NRS score for neck pain and EQ5D index of the participants were 3.0 and 0.738 points, respectively. A study that followed the postoperative course of patients who underwent cervical spine surgery showed that the NRS score for neck pain and EQ5D index were approximately 3 and 0.5 points, respectively, at 2 years postoperatively, with stable values at 1 and 2 years [ 26 ]. HRQOL was better among our study participants, although the neck pain intensity was similar between our study participants and those of Revesz et al’s [ 27 ] study.…”
Section: Discussionmentioning
confidence: 99%
“…We performed hierarchical multiple regression analysis, which is a multiple regression analysis in which independent variables are entered in several steps and is used to assess the extent to which the additional independent variables contribute to the improvement of the model [ 26 ], using the EQ5D index as the dependent variable. In step one, sex (0, male; 1, female), age, surgical technique (0, decompression; 1, decompression and fixation) duration of postoperative days, and NDI were used as the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, depression might make it more difficult for patients to stick to their treatment plan, exacerbating physical symptoms and resulting in poorer health outcomes[ 10 - 12 ]. Several studies have been conducted in recent years to investigate the link between dialysis and depression[ 13 - 17 ]. According to several studies[ 18 - 21 ], depression is more prevalent among dialysis patients than among the general population.…”
Section: Introductionmentioning
confidence: 99%